Achievement motivation and attitude of medical laboratory assistants to continuing education - K. S. Kichukova; T. G. Taneva (Образование и наука)
Introduction. The problem of improving competence by means of continuing education of health specialists is not sufficiently discussed and studied, especially in terms of medical laboratory assistants. The emphasis of the present study is on the ability to update achievement motivation of laboratory assistants through new opportunities and forms of continuing professional education. Their interest in continuing education indicates an aspiration for improving their professional competence with respect to innovative professional practices including dynamically changing methods, technologies and devices facilitating health examinations that reflect the highly significant results of their work for the health and life of their patients.The aim of the present research is to study the achievement motivation of students and medical laboratory technicians and its influence on the main variables and descriptors of the attitude towards continuous learning.Materials and research methods. The studied persons represent three target groups involved in continuing professional education - in-service medical laboratory assistants, heads of medical laboratories and students enrolled in the programme of Medical Laboratory Assistant at Bulgarian medical colleges. The methodological tools comprise standardised psychological tests, as well as questionnaires developed for the purposes of the specific study.Results and scientific novelty. The main results support the thesis that motivation for achievement is updated in activities and situations where professional success is subjectively important and there are clear criteria of success or failure. The interest in continuing education depends on the motivation for achievement as a tendency in various individuals.The higher achievement motivation determines a stronger need to improve professional competences, aspiration to acquire a graduate degree in their professional field, preferences to specialisations as a form of continuing learning and understanding of continuing education as a manifestation of the desire for new knowledge.The results from the study may enrich the existing research data on the application of achievement motivation theory as an explanatory model of life-long learning behaviour, which may become an effective way to tackle the rapidly ageing and half-life of knowledge in medicine and technology.Practical significance. The applicability of the results is very clearly visible in the formulated thesis of the necessary change in the educational policy in the country through new forms of continuous education of medical laboratory assistants which would update their achievement motivation and would result in increase in the efficiency of their professional functioning.